PENGARUH MUJAHADAH AN-NAFS DAN AL-BI’AH AL-IJTIMA’IYAH TERHADAP PERILAKU PENGELOLAAN KEUANGAN PRIBADI MAHASISWA (STUDI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS JAMBI) - Frisca D. Br. Silalahi; Nurida Isnaeni; Paulina Lubis (CV SWA Anugrah, 2023)
This research is entitled The Influence of Mujahadah an-nafs and Al-bi'ah Al-ijtima'iyah on Students' Personal Financial Management Behavior. This research aims to determine the influence of Mujahadah an-nafs and Al-bi'ah Al-ijtima'iyah on students' personal financial management behavior. The research method used is descriptive quantitative, with primary data sources. The population used was 3,248 students from the Faculty of Economics and Business, Jambi University, and the sample for this research was 100 students taken using proportionate stratifield random sampling. The data analysis technique used is the partial T test, coefficient of determination, and continued with multiple linear regression analysis. The results of this research show that the variables Mujahadah an-nafs and Al-bi'ah Al-ijtima'iyah partially and simultaneously influence the personal financial management behavior of students at the Faculty of Economics and Business, Jambi University.